Oxford Scholarship Online 2017
DOI: 10.1093/oso/9780198785446.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Marketization of Employment Services

Abstract: This book examines the marketization of employment services and its consequences in Denmark, Great Britain, and Germany. What concretely does marketization mean in practice? What are its effects on the services and their governance? How does marketization and its effects map against the main ‘regime types’ found in comparative social science? These questions are answered using more than 100 qualitative interviews with policymakers, managers, and front-line workers. The qualitative material in the book shows ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 0 publications
0
67
1
5
Order By: Relevance
“…Price-led competition between providers combined with clients’ intensified search for cost gains are held to result in a process of ‘marketization’ of the employment relationship. Contracting between parties seeks to predetermine many aspects of the employment relationship and repeated, cost-reducing transactions (Greer et al, 2017) add pressure to secure efficiency gains through reducing wages and employee benefits and increasing work intensity. To better understand these processes, relevant research on the sociology of markets has examined two key aspects, namely: (a) the mechanisms through which market actors make and reinforce market pressures through contract specifications; and (b) the mixed effects on markets in different regulatory environments of actors’ rule-taking and rule-breaking actions (Coe et al, 2009; Doellgast et al, 2015; Jaehrling and Méhaut, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Price-led competition between providers combined with clients’ intensified search for cost gains are held to result in a process of ‘marketization’ of the employment relationship. Contracting between parties seeks to predetermine many aspects of the employment relationship and repeated, cost-reducing transactions (Greer et al, 2017) add pressure to secure efficiency gains through reducing wages and employee benefits and increasing work intensity. To better understand these processes, relevant research on the sociology of markets has examined two key aspects, namely: (a) the mechanisms through which market actors make and reinforce market pressures through contract specifications; and (b) the mixed effects on markets in different regulatory environments of actors’ rule-taking and rule-breaking actions (Coe et al, 2009; Doellgast et al, 2015; Jaehrling and Méhaut, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Services were increasingly standardized in part because the funder developed a national catalogue of more than 40 off-the-shelf courses or schemes (‘ Standardprodukte’ ) (funder B). At the end of the research, the Bundesagentur reported concluding 13,000 contracts per year worth €2 billion (presentation, Düsseldorf, 24 April 2015), the largest market in our sample, albeit one in decline owing to austerity and less unemployment (Greer et al, 2017: Appendix C). Figure 4 summarizes this contracting market.…”
Section: The Decline Of Non-commercial Modelsmentioning
confidence: 97%
“…But a core NPM principle is the blurring of boundaries between for-profit and government (or nonprofit): non-commercial providers face pressure to become commercial. In new commercial organizations, work does not have to be deskilled or intensified, and worker representation and professional qualifications do not have to be marginalized, because tight management control systems exist from the outset (see Greer et al, 2017).…”
Section: Marketization Professional Autonomy and Service Quality In mentioning
confidence: 99%
See 2 more Smart Citations